Neuro-Inflammatory Response and Brain-Peripheral Crosstalk in Sepsis and Stroke - Bourhy, Lena; Mazeraud, Aurélien; Bozza, Fernando A.; Turc, Guillaume; Lledo, Pierre-Marie; Sharshar, Tarek (Frontiers in Immunology, 2022)
Despite recent therapeutic advances, ischemic stroke is still a leading cause of death and disability. There is renewed attention on peripheral inflammatory signaling as a way of modulating the post-ischemic neuro-inflammatory process. The immune-brain crosstalk has long been the focus for understanding the mechanisms of sickness behavior, which is an adaptive autonomic, neuroendocrine, and behavioral response to a peripheral inflammation. It is mediated by humoral and neural pathways that mainly involve the circumventricular organs and vagal nerve, respectively. In this review we address the question of how sepsis and stroke can dysregulate this adaptive response, notably by impairing the central integration of peripheral signaling, but also by efferent control of the immune response. We highlight the potential role of gut–brain and brain–spleen signaling in stroke.